Cooperative Learning with Reinforcement to Improve Student Motivation and Learning Outcomes on Praiseworthy Morals Material at MIS Ma'arif Salamal Huda - Suryani, Yani; Sulaeman, Wono; Faqori, Yudha Bima; Mawati, Yelmi; Ulfah, Yanti Nur (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to analyze the application of the Cooperative Learning model with reinforcement in improving motivation and learning outcomes in the subject of Akidah Akhlak, especially in the material of Commendable Akhlak in class 2 of MIS Ma'arif Salamal Huda. The Cooperative Learning model is a learning method that encourages cooperation between students in small groups, so that they can help each other in understanding the material. Meanwhile, providing reinforcement in the form of praise, awards, or positive feedback aims to strengthen students' motivation in learning. The combination of these two strategies is expected to create a more interactive and enjoyable learning environment for students. The method used in this study is the classroom action method (CAR) with a qualitative and quantitative approach. CAR was carried out in several cycles to see the effectiveness of the application of the Cooperative Learning model with reinforcement in stages. Data were collected through direct observation in class, interviews with teachers and students, and learning outcome tests to measure students' academic development. The results showed that the application of the Cooperative Learning model combined with reinforcement significantly increased students' learning motivation. Students became more active in group discussions, more enthusiastic in participating in learning, and more confident in expressing their opinions. In addition, student learning outcomes also increased as seen from the increase in average scores after implementing this strategy. Thus, the use of the Cooperative Learning method with reinforcement can be an alternative effective learning strategy in increasing student motivation and learning outcomes in learning Aqidah Akhlak.